The investigation on the best pracices of extreme programming (XP) quality implementation at UUMIT - Abdulrahman, Rana Alauldeen (2015)
Software engineering (SE) plays an important role for improving society‘s wellbeing through the use of high quality software. There is noted that most of the software projects are failed, due to missing or poor software development practices in software organizations. Due to this reason, having a good and sound software development methodology is crucial for software organization to satisfy stakeholder‘s requirements. One of the prevalent software development methodologies in SE is Extreme programming (XP) methodology. This methodology is an emerging SE approach, which is able to increase software quality and hence reducing software development time and cost. However, the level of application of this methodology among software developers in UUM IT centre is still unclear. Therefore, this study aims to investigate the application of XP practices in this centre. UUM IT was chosen as a case study because the role of this organization has changed to meet high demand among campus communities. Thus, research that focuses on the 12 XP practices of UUM IT is highly needed. This study was conducted using a semi–structured interview with five (5) experts from the UUM IT, to identify the successful implementation of the XP practices. The findings have shown that, most of the practices are used by UUM IT developers but need to improve. In contrast, some of the practices such as pair programming and test first programming are not used by the UUM IT developers. This is due to the nature and type of software projects involved, also because of the personality, experiences and the education level differences among developers. This study provides qualitative evident that can assist software project managers to guide them in improving software development practices for producing high quality software.